Interactive Learning Media Based on Augmented Reality to Improve Elementary School Grade V Students' Understanding of the Water Cycle Concept - Swarmahardika, Ida Komang Putra; Widiana, I Wayan (Universitas Pendidikan Ganesha, 2024)
Students' understanding of the water cycle concept remains low due to the reliance on less creative, mostly conventional learning media. This study aims to develop interactive learning media based on Augmented Reality to improve students' understanding of the concept of the water cycle in science material for grade V of elementary school. This study uses the ADDIE development model. There are two types of data used in this study, namely qualitative data and quantitative data. Product effectiveness testing was conducted using a one-group pretest-posttest design with a sample of 15 students. This study used a questionnaire to assess the feasibility, practicality, and effectiveness of Augmented Reality-based interactive learning media for enhancing elementary students' understanding of the water cycle. This study used 4 instruments: (1) validity test by material experts, (2) validity test by media experts, (3) practicality test by students, and (4) effectiveness test through observation sheets before and after using the media. The effectiveness test was carried out with a correlated t-test. The results of the study indicate that interactive learning media based on Augmented Reality for science material for grade V SD on the concept of the water cycle is declared valid, practical, and effective in improving students' understanding of the concept. Thus, the innovation of interactive learning media based on Augmented Reality is worthy of being used sustainably.